National Collegiate Athletic Association Division and primary job title of athletic trainers and their job satisfaction or intention to leave athletic training - Terranova, A. B.; Henning, J. M. (Journal of Athletic Training, 2011)
Context: Membership in the National Athletic Trainers' Association (NATA) has declined in recent years, generating much debate about professional commitment.